Nodal Solutions of the p-Laplacian with Sign-Changing Weight - Ruyun Ma; Xilan Liu; Jia Xu (Abstract and Applied Analysis)
We are concerned with determining values of , for which there exist nodal solutions of the boundary value problem , where is a sign-changing function, with . The proof of our main results is based upon global bifurcation techniques.